Joseph Bloomfield Osborn papers - Osborn, Joseph Bloomfield, 1842-1876.
Chiefly correspondence of Osborn, who served in Company F, 26th New Jersey Volunteer Infantry and in the U.S. Navy, with Osborn family members and Louise Landau (married Osborn in 1866). Also includes a diary (1862-1863) and biographical sketch of Osborn. Subjects include enlistments, camp life, training, and marches in Maryland and Virginia. Osborn also discusses discipline and morale, the attitude and condition of Confederate prisoners of war, casualties, and the effect of the Emancipation Proclamation on Union troops. Includes details on the Peninsular Campaign (1862), Battle of Fredericksburg, Va. (1862), and Battle of Chancellorsville, Va. (1863); Osborn's service aboard the USS Vanderbilt (Side-wheel steamer) in the North Atlantic and the South Atlantic Blockading squadrons; and the Fort Fisher, N.C., expedition of January 1865.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Soldier and sailor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Landau, Louise -- Correspondence; Osborn family -- Correspondence; Confederate States of America. -- Army; United States. -- Army; United States. -- Army -- Recruiting, enlistment, etc; United States. -- Army -- Military life; United States. -- Army. -- New Jersey Infantry Regiment, 26th (1862-1863); United States. -- Navy. -- North Atlantic Blockading Squadron (1861-1865); United States. -- Navy. -- South Atlantic Blockading Squadron (1861-1865); United States. -- President (1861-1865 : Lincoln).; Vanderbilt (Side-wheel steamer); Chancellorsville, Battle of, Chancellorsville, Va., 1863.; Fredericksburg, Battle of, Fredericksburg, Va., 1862.; Peninsular Campaign, 1862.; Slaves -- Emancipation -- United States; Fort Fisher (N.C. : Fort) -- Capture, 1865.; Maryland -- History -- Civil War, 1861-1865.; North Carolina -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865 -- Psychological aspects; Virginia -- History -- Civil War, 1861-1865.; Sailors; Soldiers